Perspectives on a sustainable future. (12th May 2004) - Rotmans, Jan; van Asselt, Marjolein B.A.
This paper presents an integrated assessment study into global change and sustainable development. A global, integrated assessment model called TARGETS, is used to develop a range of global futures. The model is intended to assess a number of the most important links between social, economic and environmental processes on a global scale. A unique feature of the TARGETS model is that it contains more than one perspective. Using a framework, a number of perspectives (consisting of worldviews and management styles) have been built in. In this way, so-called perspective-based model routes are created: chains of consistent interpretations of salient uncertainties coloured according to the various perspectives. With the help of these model routes, a number of global future trends are generated for the issues of population and health, energy, land use, water use, and biogeochemical cycles. By exploring to what extent these future directions involve certain levels of risk, an appraisal is made whether they are sustainable.